Effect of Normobaric Oxygen Inhalation Intervention on Microcirculatory Blood Flow and Fatigue Elimination of College Students After Exercise - Peng, Yong; Meng, Liang; Zhu, Huan; Wan, Li; Chen, Fen (Frontiers in Genetics, 2022)
Objective: To explore the effect of normobaric oxygen inhalation intervention on microcirculatory blood flow of college students after exercise and the impact of the elimination of exercise-induced fatigue, to provide a theoretical and methodological reference for the rapid elimination of fatigue of college students after endurance exercise. Methods: Forty-eight male non-sports majors of Hubei University for nationalities were randomly divided into the control group (n = 24) and intervention group (n = 24). The subjects in both groups completed the same exercise program twice (running 3,000 m on the treadmill at maximum speed). After running, the issues in the intervention group inhaled portable oxygen for 30 min, and the control group recovered naturally. Microcirculatory blood flow (MBP), blood flow velocity (AVBC), blood flow concentration (CMBC), muscle oxygen saturation (SmO2), heart rate (HR), blood lactic acid (BLA), blood urea (BU), and creatine kinase (CK) were measured before exercise, immediately after exercise and 30 min after exercise. Results: 1) MBP and AVBC had interaction between groups and time before and after exercise, MBP and AVBC immediately after exercise in the intervention group were significantly higher than those before exercise and 30 min after exercise, and 30 min after exercise in the intervention group were significantly higher than those in the control group. 2) SmO2, HR, BLA, BU, and CK had interaction between groups and time, and SmO2 immediately after exercise in the intervention group was significantly lower than that before exercise and 30 min after exercise, but significantly higher than that in the control group at 30 min after exercise. The HR and BLA immediately after exercise in the intervention group were significantly higher than those before exercise and 30 min after exercise, but significantly lower than those in the control group at 30 min after exercise, and the BU and CK in the intervention group were significantly higher than those before exercise, but significantly lower than those in the control group at 30 min after exercise. Conclusion: Normobaric oxygen inhalation for 30 min after exercise can delay the decrease of microcirculatory blood flow, increase muscle oxygen saturation, and promote the recovery of heart rate, blood lactic acid, blood urea and creatine kinase. Therefore, normobaric oxygen inhalation for 30 min after exercise can be used as an effective means to promote the elimination of exercise-induced fatigue after endurance running.